Strengthening Social Studies for Pancasila 5.0, Backgrounded by 'Society 5.0' - Christine Pheeney (Social Studies Conference Proceedings, 2022)
Strengthening Social Studies for Pancasila 5.0, Backgrounded by 'Society 5.0' Presented by Christine Pheeney from Charles Darwin University